Design Optimization of Composite Plate under Transverse Loading using Ritz Method. (2020) - Dhurvey, Priyanka; Kumar Patidar, Anil; Soni, Sanjay
Abstract: MATLAB program is developed using classical laminate theory, along with Ritz solution, for especially orthotropic laminates. The minimization of deflection of the symmetrical composite plate with transverse loading for clamped edge boundary conditions is the main motive of the present study for different design parameters. In order to observe the effects of various design parameters like fiber orientation, aspect ratio and thickness ratio of the plate on maximum deflection, two different plates of four layered and ten layered symmetrical composite plates are used. For optimization study, developed MATLAB program calculates the optimum fiber orientation and thickness of plies for the different parameters. This developed MATLAB program is further used to analyze hybrid laminates. The developed MATLAB programs can check all the combination possible and effectively minimize the maximum deflection of plate with optimum fibers of different material, ply thickness, fiber angles. For present study around eighteen thousand combinations were checked to give optimized composite plate.